EMPIRICAL STUDY ON EMPLOYEE’S PSYCHOLOGICAL CAPITAL: BASED ON GUANGDONG TECHNOLOGY ENTERPRISES IN CHINA - Bhaumik, Amiya (International Journal of Psychosocial Rehabilitation, 2020)
This study focuses on the relationship between psychological capital structure, psychological capital and related factors of Guangdong Technology enterprises employees. It has important theoretical and practical significance for enterprises to understand, enhance their psychological capital and improve their core competitiveness. This study collected 1640 psychological capital initial response items from 301 technicians in Guangdong Province through personal interviews, group interviews and questionnaires. Concluded 30 initial psychological capitals from behavioral events. Entries; Obtain 65 initial capital capital entries through content analysis. The structure was further validated in the following 412 valid samples of 40 technology companies in Guangdong Province. The results was evident that the five-dimensional high-order psychological capital structure has good discriminant validity and convergence validity, and its reliability coefficient reaches the psychological measurement standard. After using correlation analysis, regression analysis, exploratory factor analysis, confirmatory factor analysis and other statistical methods, and using Excell, SPSS, AMOS and other statistical tools, we focus on the analysis and verification of the research models and related hypotheses proposed in this study. Innovatively analyzes the multiple mediating role of psychological capital in organizational support and emotional commitment, work input, and job performance, and provides important research conclusions for academic circles and management practices.The relationship between demographic variables and psychological capital is also reported in the study.